2016
DOI: 10.1071/hc16020
|View full text |Cite
|
Sign up to set email alerts
|

What supports are needed by New Zealand primary care to improve equity and quality?

Abstract: While some primary care practices have found ways to deliver quality care more equitably to their Māori and Pacific patients, others have struggled to get started or be successful. Quality Symposium attendees shared their views on barriers and success factors, both within the practice and beyond. When practices have collaborated and used their own ethnic-specific data in quality improvement techniques, they have improved Māori and Pacific health and equity. Attendees asked for greater practical support and gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…These would include lowering doctor-patient and nurse-patient ratios so that more complexity can be acknowledged, 7 variation in the make up of the primary care team mix and appropriate utilisation of team skills, [25][26][27] and specific responses to local community cultural needs. 28,29 It is important to recognise that despite the challenges faced by practice teams dealing with a concentrated case mix of complex patients and problems, there are examples of how additional strategies at practice level can produce positive results. Local New Zealand examples include a weight management programme in a very low-cost access (VLCA) practice, 30 and gout management programmes with a specific equity focus.…”
Section: Discussionmentioning
confidence: 99%
“…These would include lowering doctor-patient and nurse-patient ratios so that more complexity can be acknowledged, 7 variation in the make up of the primary care team mix and appropriate utilisation of team skills, [25][26][27] and specific responses to local community cultural needs. 28,29 It is important to recognise that despite the challenges faced by practice teams dealing with a concentrated case mix of complex patients and problems, there are examples of how additional strategies at practice level can produce positive results. Local New Zealand examples include a weight management programme in a very low-cost access (VLCA) practice, 30 and gout management programmes with a specific equity focus.…”
Section: Discussionmentioning
confidence: 99%
“…Keating offers practical advice about how to improve the ethnic equity of the primary health care superstructure. 5 Meredith-Jones et al identified one area of ethnic equity: in their study there was no significant difference between, Māori, Pacific, Asian, and European parents in their recognition of obesity in their children. 6 Our guest editorial discusses the concept of obesity or 'fatness', highlighting the four papers in this issue relating to nutritional issues.…”
mentioning
confidence: 90%
“…The key intention of the PHCS is the removal of the business emphasis in primary health thus opening the way to the development of culturally relevant models of healthcare provision and delivery. Re-structuring care teams to include allied health beyond simply nursing and medical staff; delivering education to patients on how to manage healthcare and using Pacific languages in healthcare delivery are some of the ways suggested to overcome barriers to addressing Pacific health needs (Beddoe & Deeney, 2012;Döbl, Beddoe, & Huggard, 2017;Keating & Jaine, 2016;Southwick, Kenealy, & Ryan, 2012).…”
Section: Qualitative Researchmentioning
confidence: 99%